2015
DOI: 10.1093/mmy/myv060
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and risk factors for nosocomial Non-Candida albicanscandidemia in adult patients at a tertiary care hospital in North China

Abstract: Nosocomial candidemia extends the length of hospital stay, increases the costs of medical care, and is associated with a high mortality rate. Epidemiological data that assist in the choice of initial therapy may help to improve the prognosis. The present study was undertaken to investigate the epidemiology of nosocomial candidemia and identify risk factors for nosocomial candidemia caused by C. albicans and non-albicans Candida species (NAC). A retrospective chart review was undertaken to analyze cases of noso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 35 publications
9
32
2
2
Order By: Relevance
“…Several possible risk factors have been previously identified for the development of NAC candidaemia and include prior antifungal exposure, malignancy, immunosuppressive therapy, abdominal surgery [32], presence of CVCs [26], artificial surgical implants [17], head trauma and bacterial sepsis [29]. Our finding of an association of an indwelling urinary catheter and a higher risk of BSI caused by C. albicans vs. NAC is consistent with other studies [33].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Several possible risk factors have been previously identified for the development of NAC candidaemia and include prior antifungal exposure, malignancy, immunosuppressive therapy, abdominal surgery [32], presence of CVCs [26], artificial surgical implants [17], head trauma and bacterial sepsis [29]. Our finding of an association of an indwelling urinary catheter and a higher risk of BSI caused by C. albicans vs. NAC is consistent with other studies [33].…”
Section: Discussionsupporting
confidence: 90%
“…associated with candidaemia varies greatly in different regions of the world. In recent years, some studies [810, 1517] have observed a shift from the more antifungal susceptible type species C . albicans towards NAC spp., and this is corroborated by the findings of this 6-year study where NAC isolates accounted for the majority (64.4%) of all adult candidaemia episodes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies had reported the epidemiology of Candida infections in China, they mainly focused on adults, invasive Candida infections or conducted among special groups [1417]. The investigation about Candida albicans ( C.albicans ) compared to non-C.albicans candidemia in neonatal groups are limited in China [18].…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, there is a paucity of data on detailed clinical and epidemiological features of PLABSI, such as predictive factors. Moreover, studies on the epidemiology of candidemia in Asian countries, especially in Japan, are limited [2123]. …”
Section: Introductionmentioning
confidence: 99%